2011
DOI: 10.1017/s0007114511006167
|View full text |Cite
|
Sign up to set email alerts
|

Glucose tolerance factor extracted from yeast: oral insulin-mimetic and insulin-potentiating agent: in vivo and in vitro studies

Abstract: In search for an effective oral treatment for diabetes, we examined the capacity of glucose tolerance factor (GTF) extracted from yeast and administered orally to reduce hyperglycaemia in rat models exhibiting insulin deficiency. The cellular effect of GTF on the insulin signalling pathway was investigated in vitro. GTF (oral bolus), insulin (intraperitoneal) or their combination was administered to streptozotocindiabetic (STZ) or hyperglycaemic Cohen diabetic-sensitive (hyp-CDs) rats. Blood glucose (BG) and i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
31
0
1

Year Published

2012
2012
2019
2019

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 27 publications
(39 citation statements)
references
References 27 publications
(67 reference statements)
7
31
0
1
Order By: Relevance
“…They found a stimulation of glucose uptake (5.6 times greater than the basal level) in the absence of insulin. Our group also showed an increase in glucose transport both to yeast cells [63,64], and to animal cells [65].…”
Section: Grant and Mcmullensupporting
confidence: 65%
See 4 more Smart Citations
“…They found a stimulation of glucose uptake (5.6 times greater than the basal level) in the absence of insulin. Our group also showed an increase in glucose transport both to yeast cells [63,64], and to animal cells [65].…”
Section: Grant and Mcmullensupporting
confidence: 65%
“…In vitro studies done in our laboratory showed insulin mimetic and insulin potentiating activity for GTF [65].…”
Section: Grant and Mcmullenmentioning
confidence: 79%
See 3 more Smart Citations